Comparison of expression of the msx-1, msx-2, BMP-2 and BMP-4 genes in the mouse upper diastemal and molar tooth primordia - Turecková, J; Sahlberg, C; Aberg, T; Ruch, J V; Thesleff, I; Peterkova, R (The International journal of developmental biology, 1995)
The existence of transient putative tooth anlagen in the prospective mouse upper diastema region has been documented previously in morphological studies. By in situ hybridization we investigated the expression patterns of the msx-1, msx-2, BMP-2 and BMP-4 genes, supposed to regulate early tooth development, in day 10-14 mouse embryonic upper diastema and molar regions, using 49 series of frontal sections. On the basis of comparison of the temporo-spatial expression patterns in both diastemal and molar tooth primordia we conclude that each of the four genes was expressed at least for some period simultaneously and at a comparable developmental stage in the transient and persisting dental primordia. BMP-2 and BMP-4 expression was downregulated in the diastemal dental primordia during their regression starting at day 13. The temporo-spatial pattern of BMPs expression may be associated with the disappearance of diastemal rudiments. Contrary to the molar anlage, we did not detect msx-2 gene expression in the diastemal dental rudiments after the stage of epithelial thickening. The deficiency of the msx-2 gene products may play a role in the growth retardation of diastemal dental primordia resulting in their subsequent involution.
Keywords: Growth Substances; DNA-Binding Proteins; zubní zárodek; Embryonic and Fetal Development; Molar; Tooth Germ; těhotenství; Homeodomain Proteins; Gestational Age; Diastema; růstové látky; Mice; Mice, Inbred Strains; Bone Morphogenetic Proteins; Transcription Factors; myši inbrední CBA; embryonální a fetální vývoj; diastema; inbrední kmeny myší; proteosyntéza; Protein Biosynthesis; moláry; Transcription, Genetic; genetická transkripce; gestační stáří; transkripční faktory; ženské pohlaví; transkripční faktor MSX1; Gene Expression; zvířata; Pregnancy; MSX1 Transcription Factor; myši; kostní morfogenetické proteiny; Mice, Inbred CBA; DNA vazebné proteiny; exprese genu; Female; homeodoménové proteiny; Animals